Analisis Pendapatan Pedagang di Pasar Jimbaran Kelurahan Jimbaran - Chintya, Wuri Ajeng; Darsana, Ida Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 6, Juni 2013 (pp. 277-313), 2013)
A group of young people trying to survive with "trade" seeking profits through selling a variety of goods . This research aims to find out how the influence of variables that affect income traders. This study examines the factors that influence income traders such as hours of work, working capital, location and product type. This research was conducted in the village of Jimbaran, Kuta South District. Researchers using a sample with a total 106 respondents using a Stratified Random Sampling method. This study used multiple linear regression analysis. The results of this research show that the variables that affect revenue is working hours, working capital, business location and product type. Hours of work are the dominant factor affecting the market traders in Jimbaran.
Keywords: Income; Merchant; Market